El Estatuto Constitucional del no nacido: evolución y situación actual en España - Gómez Montoro, Ángel José (Revista de Derecho Político, 2018)
Resumen: El presente trabajo es un análisis de cómo ha evolucionado la protección del no nacido en España desde la aprobación de la Constitución de 1978. Se centra, en particular en el estudio de la legislación y de la jurisprudencia constitucional sobre dos temas especialmente relevantes y controvertidos: la regulación del aborto, de un lado, y de la fecundación in vitro y uso de embriones, sus tejidos y órganos, de otro. Tanto el legislador como la doctrina del Tribunal Constitucional se han inclinado por una protección gradualista de la vida humana en formación que deja abiertos muchos interrogantes desde la perspectiva del derecho a la vida (art. 15 CE) y la dignidad humana (art. 10.1 CE) Summary: 1. The Introduction Of Abortion In Spain And The STC 53/1985: a) From Criminalization To Decriminalization In Certain Circumstances; b) STC 53/1985: i) Right To Life And Prenatal Life; ii) The Life Of The Unborn As A Constitutional Interest; iii) The Constitutionality Of The Indication System; iv) The Conditions For The Constitutionality Of Decriminalization; c) The New Regulation. 2. From The «Indication System» To The «System Of Deadlines»: Organic Law 2/2010 Of 3 March On Sexual And Reproductive Health And Voluntary Termination Of Pregnancy: a) The Evolution Of Abortion In Spain Under The 1985 Act; b) The Arguments For The Reform And The Context Of The New Regulation; c) The New Regulation. 3. An Open Debate: a) The Conditions For The Constitutionality Of Decriminalization; b) The Failed Reform Of The Act. 4. The Weak Protection Of The Embryo In The Legislation On In Vitro Fertilization And The Use Of Embryonic Organs And Tissues, And The SSTC 212/1996 And 116/1999: a) Act 35/1988 On Assisted Reproduction Techniques, And Act 42/1988 On Donation And Use Of Human Embryos And Fetuses And Their Cells, Tissues And Organs; b) Negation Of The Right To Life Of The Embryo And Consequences For Its Consideration As A Constitutionally Protected Legal Interest: i) The Embryo Does Not Hold The Right To Life; ii) Two New Categories: Pre-Embryos And Non-Viable Embryos And Their Legal Relevance; iii) Surplus Embryos; iv) The Absence Of Any Criminal Protection; v) A Weak Concept Of Dignity. 5. Legislative Evolution; 6. A Model For The Gradual (Dis)Protection Of Unborn Human Life. Abstract: This paper analyzes the evolution of the protection of the unborn human life in Spain since the enactment of the 1978 Constitution. It focuses, in particular, on the study of the laws and the constitutional jurisprudence on two relevant matters: the regulation of abortion; and the in vitro fertilization, the use of embryos their tissues and organs. The legislator and the decisions of the Constitutional Court have opted for gradualist protection of the embryo that leaves many questions open from the perspective of the right to life (Article 15 SC) and human dignity (Article 10.1 SC).